066 Utilising optical coherence tomography measures as surrogates for raised intracranial pressure in idiopathic intracranial hypertension. Issue 6 (27th May 2022) - Vijay, Vivek; Mollan, Susan; Mitchell, James; Alimajstorovic, Zerin; Markey, Keira; Walker, Jessica; Lyons, Hannah; Yiangou, Andreas; Brock, Kristian; Sinclair, Alex
Abstract : Aim: To determine whether Optical Coherence Tomography (OCT) of the optic nerve head in papil- loedema could act as a surrogate measure of intracranial pressure (ICP). Methods: This is a longitudinal cohort study using data collected from three randomised controlled trials, between from April 1st, 2014 to August, 1st 2019. OCT imaging and automated perimetry was followed immediately by ICP measurement on the same day. Cohort 1 utilised continuous sitting telemetric ICP monitoring (Raumedic Neurovent P-tel device) on one visit. Cohort 2 were evaluated at baseline, 3, 12 and 24 months and underwent lumbar puncture assessment of ICP. Results: 104 patients were recruited. Amongst cohort 1 (n=15), the range of OCT protocols were evaluated and optic nerve head central thickness was found to be most closely associated with ICP (right eye: p=0.017, r = 0.60; left eye: p = 0.002; r = 0.73). Subsequently, cohort 2 (n=89) confirmed the correlation between central thickness and ICP longitudinally (12 and 24 months). Finally, bootstrap surrogacy analysis noted a positive association between central thickness and ICP treatment effects at all time points (e.g. at 12 months, an decrease in central thickness of 50µm predicted a decrease in ICP of 5 cmCSF). Conclusion: OCT optic nerve head volume measures reproducibly correlates with ICP and surrogacy analysis demonstrated its ability to inform ICP changes. This data suggests that OCT can non-invasively predict ICP. soozmollan@doctors.org.uk 58